Preparation method of high-strength wear-resistant composite coating on surface of knuckle bearing

By plating the Ti film on the non -valve metal joint bearing surface and forming titanium dioxide ceramic membrane, and then the CocrFeniti high -entropy coating on its surface magnetic sputtering system, the problem of high cost and rough surface of the valve metal arthrine bearing, and realized high -strength and strong resistance The preparation of composite coating has significantly improved the comprehensive performance of the bearings and reduced costs.

CN119352020AActive Publication Date: 2025-01-24HARBIN UNIV OF SCI & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411900943.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-24
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

Valve metal joint bearings are costly and have too rough surfaces, resulting in poor overall performance.

Method used

Magnetron sputtering technology is used to coat a Ti film on the surface of non-valve metal spherical bearings, and a titanium dioxide ceramic film is formed through micro-arc oxidation, and then a CoCrFeNiTi high-entropy coating is prepared on the surface by magnetron sputtering to form a Ti/TiO2 ceramic/CoCrFeNiTi composite coating.

Benefits of technology

It significantly improves the abrasion resistance and comprehensive performance of the surface bearing surface, reducing the cost, and this method is environmentally friendly and pollution -free, suitable for large -scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352020A_ABST
    Figure CN119352020A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-strength wear-resistant composite coating on the surface of a knuckle bearing, and relates to a preparation method of a high-strength wear-resistant composite coating. The invention aims to solve the technical problems that the cost of the existing valve metal knuckle bearing is high, and the comprehensive performance of the existing valve metal knuckle bearing is poor as the surface is too rough. The high-strength wear-resistant composite coating on the surface of the joint bearing is prepared by combining magnetron sputtering with a micro-arc oxidation process, firstly, the outer spherical surface of the inner ring of the non-valve metal joint bearing is plated with a layer of Ti film through the magnetron sputtering technology, and then a super-hydrophilic titanium dioxide ceramic film which is excellent in binding force with a base body and is rough and porous in surface is obtained through micro-arc oxidation. The titanium dioxide ceramic coating is used as a micro-arc oxidation ceramic base layer, then the titanium dioxide ceramic coating is used as the base layer, and finally a CoCrFeNiTi high-entropy coating is deposited on the surface of the titanium dioxide ceramic coating through a magnetron sputtering method to fill pores of the original micro-arc oxidation ceramic base layer, so that the roughness of the working surface of the bearing is remarkably reduced, and the wear resistance of a part is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a high-strength wear-resistant composite coating. Background Art

[0002] Spherical bearings are key load-bearing components of mechanical devices. They are located in the core parts of various mechanical devices and are widely used in equipment, automotive products, and special working condition robots. Among them, the working conditions required for carrier-based aircraft load-bearing spherical bearings are the most demanding. Spherical bearings are the core components that determine the operation of the main engine of carrier-based aircraft. They are responsible for ensuring that they can run quickly and smoothly during various flight actions of carrier-based aircraft. These bearings are often subjected to extremely high pressure, temperature, and friction during service. At the same time, they must maintain high precision and long life to ensure the safety and reliability of the flight, take-off and landing of carrier-based aircraft. Therefore, the surface wear resistance of carrier-based aircraft spherical bearings is very important. Surface modification of bearings through the design of new surface materials can greatly improve the wear resistance of bearings, thereby increasing the service life and service performance of bearings.

[0003] As a type of physical vapor deposition, magnetron sputtering technology is characterized by high deposition rate, low deposition temperature, uniform and smooth film layer, but poor bonding with the substrate. Micro-arc oxidation technology, on the other hand, is based on anodic oxidation and applies high voltage to break down the dielectric layer of the passivation film to produce arc discharge phenomenon. The high temperature and high pressure generated by arc discharge and the in-situ breakdown reaction of the material are used to obtain a ceramic film layer. It mainly oxidizes valve metals (metals with a wide passivation voltage range and capable of generating thicker and denser oxide films). When the valve metal is used as the anode, the surface will undergo anodic oxidation to generate a passivation film, thereby significantly enhancing the hardness of the material and forming a hydrophilic surface microstructure. When the valve metal is used as the anode, the ceramic film layer prepared has excellent bonding with the substrate and good wear resistance and corrosion resistance. However, although the surface with many pores and roughness is easy to form a super-hydrophilic surface, the overly rough surface has a great harm to its comprehensive performance. In addition, the cost of valve metal is relatively high, and valve metal without a fixed grade is difficult to arc during micro-arc oxidation and is not easy to form an oxide film.

[0004] Non-valve metal 42CrMo is the mainstream application product brand on the market. Its machining technology is more mature and suitable for mass production. In addition, the modulation treatment (quenching and tempering, etc.) process of 42CrMo bearing steel is more mature. Compared with other valve metal bearings, it can better meet the special use requirements under various working conditions. Summary of the invention

[0005] The present invention aims to solve the technical problems that the current valve metal spherical bearings have high costs and their overly rough surfaces lead to poor overall performance, and to provide a method for preparing a high-strength and wear-resistant composite coating on the surface of the spherical bearings.

[0006] The method for preparing the high-strength wear-resistant composite coating on the surface of the spherical bearing of the present invention is carried out according to the following steps: 1. Fix the pre-treated spherical plain bearing parts in the vacuum chamber of the magnetron sputtering equipment, use the Ti target as the cathode for magnetron sputtering, and prepare the Ti coating on the outer surface of the working surface of the inner ring of the spherical plain bearing; The material of the spherical bearing is non-valve metal; 2. The spherical bearing parts with Ti coating on the surface obtained in step 1 are placed in a micro-arc oxidation electrolyte as an anode for micro-arc oxidation after sealing and insulation treatment, so as to obtain a titanium dioxide ceramic film on the Ti film; 3. After cleaning the surface of the test piece obtained in step 2, it is placed in the magnetron sputtering vacuum chamber again, and a CoCrFeNiTi high entropy coating is prepared on the micro-arc oxide layer by magnetron sputtering to form a three-layer composite coating.

[0007] Invention design principle: The present invention adopts magnetron sputtering combined with micro-arc oxidation process to prepare a high-strength wear-resistant composite coating on the surface of the joint bearing. First, a layer of Ti film (valve metal) is plated on the outer spherical surface of the inner ring of the non-valve metal joint bearing by magnetron sputtering technology, and then the high temperature and high pressure generated by the arc discharge during micro-arc oxidation and the in-situ breakdown reaction of the material are used to obtain a super-hydrophilic titanium dioxide ceramic film with excellent bonding strength with the substrate and a rough and porous surface. This layer is then used as a base layer, and the porous characteristics of the ceramic film are used to improve the bonding strength between the coating and the bearing substrate. The advantages of the porous structure are used to enhance the wettability of the subsequent film and improve the bonding strength. ; Then, a CoCrFeNiTi high-entropy coating was deposited on the surface of the titanium dioxide ceramic coating by magnetron sputtering to fill the pores of the original micro-arc oxidation ceramic base layer, which significantly reduced the roughness of the bearing working surface and improved the wear resistance of the parts. At the same time, due to the "cocktail" harmonizing effect of the high-entropy alloy, the coating structure has the multi-component advantages of high-entropy materials. Because the high-entropy film contains Ti element, the compatibility of the high-entropy layer and the micro-arc oxidation layer is improved, thereby improving the bonding quality. Finally, a Ti / TiO2 ceramic / CoCrFeNiTi composite coating with strong comprehensive surface performance is obtained.

[0008] The main functions of the three solutes in the micro-arc oxidation electrolytic solution in step 2 of the present invention are: Na3PO4·12H2O provides phosphate ions (PO4 3-), can increase the solution conductivity to a certain extent, and form a thinner initial passivation film, soften the subsequent breakdown arc, and reduce the micro-area discharge area to obtain a continuous and smooth oxide film; but excessive phosphate ions will cause the discharge energy to gather in the local micro-area, resulting in macroscopic weak arc damage in many parts of the film layer, so the content of Na3PO4·12H2O is selected as: Na3PO4·12H2O 8.67g / L. Na2SiO3·9H2O provides silicate ions (SiO3 2- ), which greatly increases the solution conductivity, reduces the arc starting voltage, and is easy to form a passivation film; at the same time, silicate (SiO3 2- ) can work synergistically with other anions in the electrolyte to intensify the contrast of the microscopic potential strength and weakness zones on the anode surface, promote the stability of the discharge spark alternation, and avoid the occurrence of macroscopic burning caused by local overheating. Under comprehensive conditions, the content of NaSiO3·9H2O is selected as: 9.34g / L. NaF acts as a complexing agent in the solution. A small amount of NaF can improve the stability of the solution, delay the precipitation of precipitates, ensure the long-term effect of the electrolyte, and maintain the continuous stability of the discharge process. Therefore, the content of NaF is: 1g / L.

[0009] The present invention has the following beneficial effects: 1. In the Ti / TiO2 ceramic / CoCrFeNiTi composite coating structure prepared by the present invention, the Ti / TiO2 ceramic layer located in the bottom layer forms a porous hard interface on the bearing surface, which exhibits super-hydrophilic properties, greatly enhancing the bonding strength between the subsequent high-entropy coating and the bearing parts, and also provides a high-strength hard protective phase for the substrate, thereby significantly improving the wear resistance; 2. In the Ti / TiO2 ceramic / CoCrFeNiTi composite coating structure prepared by the present invention, the CoCrFeNiTi composite coating is a composite high entropy alloy material composed of Cantor alloy and multiple strengthening elements. In addition to good wear resistance, it has excellent oxidation resistance, high temperature resistance and corrosion resistance, and is the most prominent application in the surface modification materials of bearing parts; 3. Compared with traditional coating preparation methods, the micro-arc oxidation electrolyte does not contain heavy metals, has strong anti-pollution ability, and can be recycled, meeting the clean production standards; the magnetron sputtering process is environmentally friendly, pollution-free, and does not produce harmful waste; 4. The present invention adopts magnetron sputtering technology and micro-arc oxidation technology, the equipment is simple, easy to operate, suitable for continuous operation and large-scale production, and can be industrially applied. Both technologies have conformal processing characteristics and have good coating preparation and deposition efficiency for spherical bearings and other special structural parts; 5. The material of the spherical bearing used in the present invention is non-valve metal, and the cost is greatly reduced compared with valve metal. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 This is a real photo of the spherical plain bearing in step 1 of test 1; Figure 2 This is a schematic diagram of the sealing and insulation treatment in step 2 of experiment 1; Figure 3 It is a comparison diagram of the friction coefficient curves of the CoCrFeNiTi composite coating with a micro-arc oxidation primer prepared in the first test and the CoCrFeNiTi composite coating without a micro-arc oxidation primer prepared in the comparative test; Figure 4 SEM comparison images of the CoCrFeNiTi composite coating with micro-arc oxidation primer prepared in experiment 1 and the CoCrFeNiTi composite coating without micro-arc oxidation primer prepared in the comparative experiment after the above-mentioned friction and wear test. DETAILED DESCRIPTION

[0011] Specific implementation method 1: This implementation method is a method for preparing a high-strength wear-resistant composite coating on the surface of a spherical bearing, which is specifically carried out according to the following steps: 1. Fix the pre-treated spherical plain bearing parts in the vacuum chamber of the magnetron sputtering equipment, use the Ti target as the cathode for magnetron sputtering, and prepare the Ti coating on the outer surface of the working surface of the inner ring of the spherical plain bearing; The material of the spherical bearing is non-valve metal; 2. The spherical bearing parts with Ti coating on the surface obtained in step 1 are placed in a micro-arc oxidation electrolyte as an anode for micro-arc oxidation after sealing and insulation treatment, so as to obtain a titanium dioxide ceramic film on the Ti film; 3. After cleaning the surface of the test piece obtained in step 2, it is placed in the magnetron sputtering vacuum chamber again, and a CoCrFeNiTi high entropy coating is prepared on the micro-arc oxide layer by magnetron sputtering to form a three-layer composite coating.

[0012] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the pre-treatment process of the spherical bearing described in step 1 is: grinding the working surface of the inner ring of the spherical bearing with 400#, 800#, 1500# and 2000# sandpaper in sequence, then polishing, and then ultrasonically cleaning in anhydrous ethanol for 15 minutes, and drying with a hair dryer. The rest is the same as specific implementation method 1.

[0013] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: in step 1, the inner ring axis of the spherical bearing is fixed to the motor shaft of the sample stage so that the two rotate coaxially. The rest is the same as specific implementation method 1 or 2.

[0014] Specific embodiment 4: This embodiment is different from specific embodiment 3 in that the background vacuum in the magnetron sputtering process described in step 1 is 5×10 -3 Pa, the working gas is argon, the working gas pressure is 1Pa, the bias voltage is 80V, the sputtering frequency of the Ti target is 150W, the sputtering time is 1h, and the outer spherical surface of the inner ring of the spherical bearing is evenly coated with the Ti coating material by using the sample stage motor. The rest is the same as the specific implementation method three.

[0015] Specific implementation method 5: This implementation method is different from specific implementation method 4 in that: the method of sealing and insulating the joint bearing parts in step 2 is: connect the aluminum wire led out of the anode of the micro-arc oxidation pulse power supply to the non-working surface of the inner ring of the joint bearing with transparent tape and UV glue, and seal and insulate the non-working surface of the inner ring of the joint bearing with transparent tape and UV glue so that the electrolyte only contacts the working surface of the inner ring. The rest is the same as specific implementation method 4.

[0016] Specific embodiment 6: This embodiment is different from specific embodiment 5 in that the cathode in the micro-arc oxidation described in step 2 is a cast iron ring, and the pulse power supply adopts a constant current mode. The rest is the same as specific embodiment 5.

[0017] Specific implementation method 7: The difference between this implementation method and specific implementation method 6 is that the parameters of the pulse power supply described in step 2 are set to a positive voltage of 590V, a negative voltage of 200V, and a current density of 5A / dm 2 , the frequency is 1000 Hz, the positive duty cycle is 50%, the negative duty cycle is 0%, and the oxidation time is 25 seconds. The rest is the same as the sixth embodiment.

[0018] Specific embodiment 8: This embodiment differs from specific embodiment 7 in that the concentration of the solute in the electrolyte described in step 2 is as follows: Na3PO4·12H2O is 8.67 g / L, Na2SiO3·9H2O is 9.34 g / L, NaF is 1 g / L, and the solvent is deionized water. Others are the same as specific embodiment 7.

[0019] Specific embodiment 9: This embodiment is different from specific embodiment 8 in that a CoCrFeNi target and a Ti target are used as cathodes in the magnetron sputtering process described in step 3. The rest is the same as specific embodiment 8.

[0020] Specific embodiment 10: This embodiment differs from specific embodiment 9 in that the background vacuum of the magnetron sputtering described in step 3 is 5×10 -3 Pa, the working gas pressure is 1 Pa, the bias voltage is 80 V, the sputtering frequency of the CoCrFeNi target is 100 W, the sputtering frequency of the Ti target is 150 W, and the sputtering time is 1.5 h. Others are the same as those in the ninth embodiment.

[0021] The present invention is verified by the following tests: Test 1: This test is a method for preparing a high-strength wear-resistant composite coating on the surface of a spherical bearing, which is specifically carried out in the following steps: 1. Fix the pre-treated spherical plain bearing parts in the vacuum chamber of the magnetron sputtering equipment as the anode, use the Ti target as the cathode for magnetron sputtering, and prepare the Ti coating on the outer surface of the working surface of the inner ring of the spherical plain bearing; The material of the spherical bearing is non-valve metal 42CrMo, and its structure is as follows: Figure 1 As shown, 1 is the outer ring and 2 is the inner ring; The pre-treatment process of the spherical bearing is as follows: grinding the working surface of the inner ring of the spherical bearing with 400#, 800#, 1500# and 2000# sandpaper in turn, polishing, ultrasonic cleaning in anhydrous ethanol for 15 minutes, and drying with a hair dryer; Fix the inner ring axis of the spherical bearing on the motor shaft of the sample stage so that the two rotate coaxially; The background vacuum during the magnetron sputtering process is 5×10 -3 Pa, the working gas is argon, the working gas pressure is 1Pa, the bias voltage is 80V, the sputtering frequency of the Ti target is 150W, the sputtering time is 1h, and the outer spherical surface of the inner ring of the spherical bearing is evenly coated with the Ti coating material by using the sample stage motor; 2. The spherical bearing parts with Ti coating on the surface obtained in step 1 are suspended in a micro-arc oxidation electrolyte as an anode for micro-arc oxidation after sealing and insulation treatment, so as to obtain a titanium dioxide ceramic film on the Ti film; The method of sealing and insulating the joint bearing parts in step 2 is as follows: Figure 2 As shown (the outer ring of the spherical bearing is removed for a more intuitive photo, and only the inner ring is shown in the figure), the aluminum wire 6 led out of the anode of the micro-arc oxidation pulse power supply is connected to the non-working surface of the inner ring of the spherical bearing with transparent tape 4 and UV glue 5, and the non-working surface of the inner ring of the spherical bearing is sealed and insulated with transparent tape 4 and UV glue 5 so that the electrolyte only contacts the working surface 3 of the inner ring; The cathode in the micro-arc oxidation described in step 2 is a cast iron ring, and the pulse power supply adopts a constant current mode. The parameters of the pulse power supply are set to a positive voltage of 590V, a negative voltage of 200V, and a current density of 5A / dm 2 , frequency is 1000Hz, positive duty cycle is 50%, negative duty cycle is 0%, and oxidation time is 25s; The concentrations of the solutes in the electrolyte described in step 2 are as follows: 8.67 g / L for Na3PO4·12H2O, 9.34 g / L for Na2SiO3·9H2O, 1 g / L for NaF, and the solvent is deionized water; 3. After cleaning the surface of the test piece obtained in step 2, the test piece is placed in the magnetron sputtering vacuum chamber again, and a CoCrFeNiTi high entropy coating is prepared on the micro-arc oxide layer by magnetron sputtering to form a three-layer composite coating; In the magnetron sputtering process described in step 3, a CoCrFeNi target and a Ti target are used together as cathodes; The background vacuum of the magnetron sputtering described in step 3 is 5×10 -3 Pa, the working gas pressure is 1Pa, the bias voltage is 80V, the sputtering frequency of the CoCrFeNi target is 100W, the sputtering frequency of the Ti target is 150W, and the sputtering time is 1.5h.

[0022] The operation of magnetron sputtering in steps one and three includes the following steps: 1) Turn on the magnetron sputtering instrument and open the vent valve; 2) After opening the vacuum chamber, fix the spherical bearing parts to the sample stage rotating fixture on the anode target, and put the cathode into the cathode target; 3) Turn on the air pump, gas cylinder, and water chiller to ensure stable operation of the equipment; 4) After closing the door, open the mechanical pump and the bypass valve to extract the vacuum, and then turn on the molecular pump to ensure the vacuum degree in the vacuum chamber; 5) After turning on the cathode target MPC power supply, open the gas inlet valve and flush in argon gas; 6) When the gate opening degree shows 200%, close the M-plate valve to control the working gas flow; 7) Adjust voltage power and add bias; 8) Open the baffle of the cathode target, start the sample stage to rotate, ensure that the bearing parts are evenly coated, and start coating; 9) After coating is completed, close the above devices in sequence and take out the sample.

[0023] Comparative test: This test is a method for preparing a CoCrFeNiTi composite coating without a micro-arc oxidation primer, which is specifically carried out in the following steps: The pre-treated spherical plain bearing parts were fixed in the vacuum chamber of the magnetron sputtering equipment as the anode, and the CoCrFeNi target and the Ti target were used as the cathode for magnetron sputtering to prepare the CoCrFeNiTi high entropy coating on the outer surface of the working surface of the inner ring of the spherical plain bearing; The material of the spherical bearing is non-valve metal 42CrMo; The pre-treatment process of the spherical bearing is as follows: grinding the working surface of the inner ring of the spherical bearing with 400#, 800#, 1500# and 2000# sandpaper in turn, polishing, ultrasonic cleaning in anhydrous ethanol for 15 minutes, and drying with a hair dryer; Fix the inner ring axis of the spherical bearing on the motor shaft of the sample stage so that the two rotate coaxially; The background vacuum of the magnetron sputtering is 5×10 -3 Pa, the working gas pressure is 1Pa, the bias voltage is 80V, the sputtering frequency of the CoCrFeNi target is 100W, the sputtering frequency of the Ti target is 150W, and the sputtering time is 1.5h.

[0024] Figure 3 This is a comparison chart of the friction coefficient curves of the CoCrFeNiTi composite coating with a micro-arc oxidation primer prepared in the first test and the CoCrFeNiTi composite coating without a micro-arc oxidation primer prepared in the comparative test. The tribological test was carried out on a standard friction and wear test equipment (model: MPT-3G). The pin-disc friction pair was loaded on the equivalent flat part of the spherical bearing. The bearing was fixed and the pin-disc was the friction pair rotating. The tribological performance of the bearing equivalent flat part was tested. Figure 2 The tribological curve comparison results are shown in which the average tribological coefficient of the film without primer is 0.561, and the average tribological coefficient of the film with Ti film micro-arc oxidation primer is 0.416. The friction coefficient is significantly reduced and the wear resistance is greatly improved.

[0025] Figure 4 SEM comparison images of the CoCrFeNiTi composite coating with micro-arc oxidation primer prepared in experiment 1 and the CoCrFeNiTi composite coating without micro-arc oxidation primer prepared in the comparative experiment after the above-mentioned friction and wear test. The left image is the Ti film micro-arc oxidation primer film. It can be seen that the peeling of the high-entropy film is not obvious, and the bottom layer does not expose the substrate, while the right image without primer film shows obvious substrate exposure (Fe is the main element of 42CrMo), indicating that the friction and wear experiment has damaged the parts and cannot improve the performance of the bearing well.

[0026] The present invention adopts the above-mentioned method for preparing a high-strength wear-resistant composite coating on the surface of a joint bearing, complementing the advantages of magnetron sputtering technology and micro-arc oxidation technology, and obtaining a composite coating with excellent wear resistance, which can effectively protect the bearing in extreme environments and greatly improve its service life.

Claims

1. A method for preparing a high-strength wear-resistant composite coating on the surface of a spherical bearing, characterized in that The preparation method of the high-strength wear-resistant composite coating on the surface of the spherical bearing is carried out according to the following steps:

1. Fix the pre-treated spherical plain bearing parts in the vacuum chamber of the magnetron sputtering equipment, use the Ti target as the cathode for magnetron sputtering, and prepare the Ti coating on the outer surface of the working surface of the inner ring of the spherical plain bearing; The material of the spherical bearing is non-valve metal; 2. The spherical bearing parts with Ti coating on the surface obtained in step 1 are placed in a micro-arc oxidation electrolyte as an anode for micro-arc oxidation after sealing and insulation treatment, so as to obtain a titanium dioxide ceramic film on the Ti film; 3. After cleaning the surface of the test piece obtained in step 2, it is placed in the magnetron sputtering vacuum chamber again, and a CoCrFeNiTi high entropy coating is prepared on the micro-arc oxide layer by magnetron sputtering to form a three-layer composite coating.

2. The method for preparing a high-strength wear-resistant composite coating on a spherical bearing surface according to claim 1, characterized in that The pretreatment process of the spherical bearing described in step 1 is: grind the working surface of the inner ring of the spherical bearing with 400#, 800#, 1500# and 2000# sandpaper in turn, then polish it, then ultrasonically clean it in anhydrous ethanol for 15 minutes, and blow dry it with a hair dryer.

3. The method for preparing a high-strength wear-resistant composite coating on a joint bearing surface according to claim 1, characterized in that In step 1, the inner ring axis of the spherical bearing is fixed on the motor shaft of the sample stage so that the two rotate coaxially.

4. The method for preparing a high-strength wear-resistant composite coating on a spherical bearing surface according to claim 3, characterized in that The background vacuum during the magnetron sputtering process described in step 1 is 5×10 -3 Pa, the working gas is argon, the working gas pressure is 1Pa, the bias voltage is 80V, the sputtering frequency of the Ti target is 150W, the sputtering time is 1h, and the sample stage motor is used to evenly coat the outer spherical surface of the inner ring of the spherical bearing with the Ti coating material.

5. The method for preparing a high-strength wear-resistant composite coating on a spherical bearing surface according to claim 1, characterized in that The method for sealing and insulating the spherical bearing parts in step 2 is: use transparent tape and UV glue to connect the aluminum wire led out of the anode of the micro-arc oxidation pulse power supply to the non-working surface of the inner ring of the spherical bearing, and use transparent tape and UV glue to seal and insulate the non-working surface of the inner ring of the spherical bearing so that the electrolyte only contacts the working surface of the inner ring.

6. The method for preparing a high-strength wear-resistant composite coating on a spherical bearing surface according to claim 1, characterized in that The cathode in the micro-arc oxidation described in step 2 is a cast iron ring, and the pulse power supply adopts a constant current mode.

7. The method for preparing a high-strength wear-resistant composite coating on a spherical bearing surface according to claim 6, characterized in that The parameters of the pulse power supply described in step 2 are set to positive voltage of 590V, negative voltage of 200V, and current density of 5A / dm 2 , frequency is 1000Hz, positive duty cycle is 50%, negative duty cycle is 0%, and oxidation time is 25s.

8. The method for preparing a high-strength wear-resistant composite coating on a spherical bearing surface according to claim 1, characterized in that The concentrations of the solutes in the electrolyte described in step 2 are as follows: Na3PO4·12H2O is 8.67 g / L, Na2SiO3·9H2O is 9.34 g / L, NaF is 1 g / L, and the solvent is deionized water.

9. The method for preparing a high-strength wear-resistant composite coating on a spherical bearing surface according to claim 1, characterized in that In the magnetron sputtering process described in step three, a CoCrFeNi target and a Ti target are used together as cathodes.

10. The method for preparing a high-strength wear-resistant composite coating on a spherical bearing surface according to claim 9, characterized in that The background vacuum of the magnetron sputtering described in step 3 is 5×10 -3 Pa, the working gas pressure is 1Pa, the bias voltage is 80V, the sputtering frequency of the CoCrFeNi target is 100W, the sputtering frequency of the Ti target is 150W, and the sputtering time is 1.5h.

Citation Information

Patent Citations

  • Preparation method of TiO2 depositing layer on stainless steel surface

    CN103388122A

  • Method for improving wear resistant property of metal material

    CN103981498A

  • Micro-arc oxidation method for surfaces of copper, copper alloy, zinc and zinc alloy

    CN105331941A

  • Preparation method of AlCrCuFeNi high-entropy alloy bearing coating

    CN108411272A

  • Titanium alloy wear-resistant and antibacterial composite coating suitable for marine environment and preparation method of titanium alloy wear-resistant and antibacterial composite coating

    CN114318467A